Absorption of EU Funds in the context of Polish enterprises competitiveness measured by profitability rates - Anna Wildowicz-Giegiel; Adam Wyszkowski (Institute of Economic Research (IER), 2014)
Competitiveness at the firm level is a subject of interest not only to managers and policy makers but also academics. An effective functioning under the conditions of new economy requires from the enterprises to develop their core capabilities and talents along with the ability to quickly identify and seize the opportunities generated by market environment. The implementation of such an approach allows the creation and sustain of economic surpluses in the long-run. The paper aims to examine the profitability of enterprises in Poland which is regarded in the context of absorption of EU funds in years 2007-2013. Taking into account that Poland became one of the largest beneficiaries, it is worth analyzing the impact of EU funding on the economic performance of Polish enterprises. The paper offers a critical reflection on the relationship between the absorption of EU funds and Polish enterprises competitiveness on the basis of the content analysis literature and statistical data derived from the European Commission, the Central Statistical Office and the Ministry of Infrastructure and Development. It is assumed simultaneously that the competitiveness of enterprises is expressed in the term of profitability rates. In spite of limitations which relate to the adopted definition of competitiveness and the short period of the conducted analysis concerning the key relationship, the paper contributes to the debate on the significance of EU Funds in the process of building modern and innovative economy.
Keywords: D21; D92; P17; N41; 330; financial results; profitability; competitiveness; EU Funds